Identification of Putative ORF5 Protein of Porcine Circovirus Type 2 and Functional Analysis of GFP-Fused ORF5 Protein - Lv, Qizhuang (PLoS One, 2015)
Porcine circovirus type 2 (PCV2) is the essential infectious agent responsible for causing porcine circovirus-associated diseases in pigs. To date, eleven RNAs and five viral proteins of PCV2 have been detected. Here, we identified a novel viral gene within the PCV2 genome, termed ORF5, that exists at both the transcriptional and translational level during productive infection of PCV2 in porcine alveolar macrophages 3D4/2 (PAMs). Northern blot analysis was used to demonstrate that the ORF5 gene measures 180 bp in length and overlaps completely with ORF1 when read in the same direction. Site-directed mutagenesis was used to show that the ORF5 protein is not essential for PCV2 replication. To investigate the biological functions of the novel protein, we constructed a recombinant eukaryotic expression plasmid capable of expressing PCV2 ORF5. The results show that the GFP-tagged PCV2 ORF5 protein localizes to the endoplasmic reticulum (ER), is degraded via the proteasome, inhibits PAM growth and prolongs the S-phase of the cell cycle. Further studies show that the GFP-tagged PCV2 ORF5 protein induces ER stress and activates NF-κB, which was further confirmed by a significant upregulation in IL-6, IL-8 and COX-2 expression. In addition, five cellular proteins (GPNMB, CYP1A1, YWHAB, ZNF511 and SRSF3) were found to interact with ORF5 via yeast two-hybrid assay. These findings provide novel information on the identification and functional analysis of the PCV2 ORF5 protein and are likely to be of benefit in elucidating the molecular mechanisms of PCV2 pathogenicity. However, additional experiments are needed to validate the expression and function of the ORF5 protein during PCV2 infection in vitro before any definitive conclusion can be drawn.